The natural history of de novo donor-specific HLA antibodies after kidney transplantation - López del Moral, Covadonga; Wu, Kaiyin; Naik, Marcel; Osmanodja, Bilgin; Akifova, Aylin; Lachmann, Nils; Stauch, Diana; Hergovits, Sabine; Choi, Mira; Bachmann, Friederike; Halleck, Fabian; Schrezenmeier, Eva; et al. (Frontiers in Medicine, 2022)
De novo donor-specific antibodies (dnDSA) are key in the diagnosis of antibody-mediated rejection (ABMR) and related to graft loss. This retrospective study was designed to evaluate the natural course of dnDSA on graft function and kidney allograft survival and to assess the impact of mean fluorescence intensity (MFI) evolution as detected by annual Luminex® screening. All 400 kidney transplant recipients with 731 dnDSA against the last graft (01/03/2000-31/05/2021) were included. During 8.3 years of follow-up, ABMR occurred in 24.8% and graft loss in 33.3%, especially in patients with class I and II dnDSA, and those with multiple dnDSA. We observed frequent changes in MFI with 5-year allograft survivals post-dnDSA of 74.0% in patients with MFI reduction ≥50%, 62.4% with fluctuating MFI (MFI reduction ≥50% and doubling) and 52.7% with doubling MFI (log rank p<0.001). Interestingly, 168 (24.3%) dnDSA became negative at some point during follow-up and 38/400 (9.5%) patients became stable negative, which was associated with better graft survival. Multivariable analysis revealed the importance of MFI evolution and rejection, while class and number of dnDSA were not contributors in this model. In summary, we provide an in-depth analysis of the natural course of dnDSA after kidney transplantation, first evidence for the impact of MFI evolution on graft outcomes and describe a relevant number of patients with a stable disappearance of dnDSA, related to better allograft survival.